Changes in the Framing of Antimicrobial Resistance in Print Media in Australia and the United Kingdom (2011-2020): A Comparative Qualitative Content and Trends Analysis - Chris Degeling; Victoria Brookes; Tarant Hill; Julie Hall; Anastacia Rowles; Cassandra Tull; Judy Mullan; Mitchell Byrne; Nina Reynolds; Olivia Hawkins (MDPI AG, 2021)
Educating the public about antimicrobial resistance (AMR) is considered a key part of an optimal public health response. In both media depictions and policy discourses around health risks, how a problem is framed underpins public awareness and understanding, while also guiding opinions on what actions can and should be taken. Using a mixed methods approach we analyse newspaper content in Australia and the United Kingdom (UK) from 2011 to 2020 to track how causes, consequences and solutions to AMR are represented in countries with different policy approaches. Analyses demonstrate greater variability in the frames used in UK newspapers reflecting large hospital and community outbreaks and a sustained period of policy reform mid-decade. Newspapers in Australia focus more on AMR causes and consequences, highlighting the importance of scientific discovery, whereas UK coverage has greater discussion of the social and economic drivers of AMR and their associated solutions. Variations in the trends of different frames around AMR in UK newspapers indicate greater levels of public deliberation and debate around immediate and actionable solutions; whereas AMR has not had the same health and political impacts in Australia resulting in a media framing that potentially encourages greater public complacency about the issue.